3x/4 - x/3
To simplify this, we need to first find a common denominator, or the Greatest Common Factor (GCF) of the two denominators (4 and 3). The GCF of 3 and 4 is 12.
Now, we have to multiply the numerator AND denominator of each individual term by the same factor such that the denominator equals 12.
So for the first term, 3x/4, we know that 12/4 = 3, therefore we need to multiply the fraction by 3/3, which is equivalent to 1.
3x/4 * 3/3 = 9x/12
Now, let's do the same for the other term x/3. We know that 12/3 = 4, therefore we need to multiply the fraction by 4/4, which is equivalent to 1.
x/3 * 4/4 = 4x/12
Now, lets substitute these equivalent fractions back into the original expression.
3x/4 - x/3 = 9x/12 - 4x/12 = 5x/12
Thus, your answer is #4, or 5x/12